Enhancing solar panel efficiency through dual-axis tracking and fresnel lens concentration: an image processing approach - Ghozi Witsqa Ramadhan, Muhammad; Halim, Levin; Wahab, Faisal (Bulletin of Electrical Engineering and Informatics, 2025)
Solar energy is currently utilized as an inexhaustible renewable energy source. Solar panels can convert solar energy into electrical energy that humans can use. The drawback of solar panels is that they cannot always be perpendicular to the sun, causing a decrease in the intensity of incoming light. Therefore, in this research, a solar tracking system with a fresnel lens was designed using image processing to increase the output of solar panels. In this research, programming was done using Python software for image processing using the hue, saturation, value (HSV) color, and space model, which was then connected with Arduino using the PyFirmata library to move the motor. In this research, solar panels with a fresnel lens and solar tracking were implemented. Data collection was performed on the output voltage of the solar panel. The research concludes that solar panels with solar tracker and fresnel lens have a higher average output voltage of 7.53 V than passive solar panels with an average output voltage of 6.38 V. Also, the average output voltage increased by 18.02% after implementing the solar tracking system and adding the fresnel lens.